Antifungal Susceptibility in Serum and Virulence Determinants of Candida Bloodstream Isolates from Hong Kong - Seneviratne, Chaminda J.; Rajan, Suhasini; Wong, Sarah S. W.; Tsang, Dominic N. C.; Lai, Christopher K. C.; Samaranayake, Lakshman P.; Jin, Lijian (Frontiers in Microbiology, 2016)
Candida bloodstream infections (CBI) are one of the most common nosocomial infections globally, and they account for a high mortality rate. The increasing global prevalence of drug-resistant Candida strains has also been posing a challenge to clinicians. In this study, we comprehensively evaluated the biofilm formation and production of hemolysin and proteinase of 63 CBI isolates derived from a hospital setting in Hong Kong as well as their antifungal susceptibility both in the presence and in the absence of human serum, using standard methodology. C. albicans was the predominant species among the 63 CBI isolates collected, and non-albicans Candida species accounted for approximately one third of the isolates (36.5%). Of them, C. tropicalis was the most common non-albicans Candida species. A high proportion (31.7%) of the CBI isolates (40% of C. albicans isolates, 10% of C. tropicalis isolates, 11% of C. parapsilosis isolates and 100% of C. glabrata isolates) were found to be resistant to fluconazole. One of the isolates (C. tropicalis) was resistant to amphotericin B. A rising prevalence of drug-resistance CBI isolates in Hong Kong was observed with reference to a previous study. Notably, all non-albicans Candida species, showed increased hemolytic activity relative to C. albicans, whilst C. albicans, C. tropicalis and C. parapsilosis exhibited proteinase activities. Majority of the isolates were capable of forming mature biofilms. Interestingly, the presence of serum distorted the yeast sensitivity to fluconazole, but not amphotericin B. Taken together, our findings demonstrate that CBI isolates of Candida have the potential to express to varying extent their virulence attributes (e.g. biofilm formation, hemolysin production and proteinase activity) and these, together with perturbations in their antifungal sensitivity in the presence of serum, may contribute to treatment complication in candidemia. The effect of serum on antifungal activity warrants further investigations, as it has direct clinical relevance to the treatment outcome in subjects with candidemia.